2021
DOI: 10.2147/dmso.s304994
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and Validation of a Prediction Model for Predicting the 5-Year Incidence of Type 2 Diabetes in Non-Obese Adults: A Population-Based Cohort Study

Abstract: The aim of this study was to derivate and validate a nomogram based on independent predictors to better evaluate the 5-year risk of T2D in non-obese adults. Patients and Methods: This is a historical cohort study from a collection of databases that included 12,940 non-obese participants without diabetes at baseline. All participants were randomised to a derivation cohort (n = 9651) and a validation cohort (n = 3289). In the derivation cohort, the least absolute shrinkage and selection operator (LASSO) regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 75 publications
(103 reference statements)
1
13
0
Order By: Relevance
“…We followed the methods of Cai et al 2021. 20 To improve the robustness and reliability of our conclusions, 3659 NAFLD patients were randomly divided into a development cohort with 2744 participants and a validation cohort with 915 participants at a ratio of 7.5: 2.5 using R caret package, which met the theoretical ratio of 3: 1. The types of data for this study are divided into measured data, non-normally distributed measured data and count data.…”
Section: Methodsmentioning
confidence: 99%
“…We followed the methods of Cai et al 2021. 20 To improve the robustness and reliability of our conclusions, 3659 NAFLD patients were randomly divided into a development cohort with 2744 participants and a validation cohort with 915 participants at a ratio of 7.5: 2.5 using R caret package, which met the theoretical ratio of 3: 1. The types of data for this study are divided into measured data, non-normally distributed measured data and count data.…”
Section: Methodsmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2DM) is a major concern in healthcare worldwide due to its high prevalence and severe complications. 1,2 In 2017, approximately 462 million people were affected by T2DM, which corresponds to a prevalence of 6059 cases per 100,000 people. It is predicted to increase to 7079 per 100,000 people by 2030, reflecting a continued rising and showing no signs of stabilization worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is an important risk factor for the onset of T2DM. 2 , 18 , 19 BMI is considered a marker for obesity and a predictor variable for most risk models of diabetes. However, studies have suggested that BMI does not reflect central obesity.…”
Section: Discussionmentioning
confidence: 99%
“… 1 It has rapidly become a serious public health problem in both developed and developing countries in recent decades due to the rise in obesity and sedentary lifestyle. 2 , 3 It has caused a tremendous burden on the global healthcare system. Studies have reported that the economic burden in the US alone was estimated at $327 billion in 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation